How to Incorporate Corporate Social Responsibility into DNA of the Companies? (European Journal of Marketing and Economics, 2022)
In my presentation I would like to treat corporate social responsibility (CSR) from a legal perspective and especially discuss how to achieve an effective application of the CSR codes and principles. In this respect I would like to discuss solution proposals such as emphasizing compliance programs or certification systems and especially the question how CSR principles could be regulated by legislations with binding character, as hard law instruments. This is also mentioned as the ultimate goal of the CSR in the summary of European Commissions Multi-Stakeholder Forum The ultimate goal of CSR should be to embed social responsibility into DNA of companies, rendering it absolete through normative compliance. Corporate Social Responsibility, is an approach that companies should conduct their business in a responsible and fair way and that they should take responsibility of their impact on society. CSR, has different pillars such as sustainability, environment, human rights, investment, public procurement etc… Among all these different subsectors, I will treat the applicability of the CSR principles mostly from the sustainability perspective. Since CSR has so many different facets and propose a general policy of good conduct rather than concrete specific rules and legal provisions, stays as a vague concept and need to be defined and concretized. CSR has no description and is not regulated in the national codes and legal systems. However, there are a lot of regulations, guidelines and standards prepared by international authorities and organizations and the European Commission.
Keywords: How to Incorporate Corporate Social Responsibility into DNA of the Companies?